Social resentment, blame attribution and Euroscepticism: the role of status insecurity, relative deprivation and powerlessness. Issue 1 (2nd January 2022) - Abts, Koen; Baute, Sharon
Abstract : This article investigates the relationship between social resentment and Euroscepticism. It argues that that populist parties mobilize the resentment of the losers of modernization by addressing new cultural and political cleavages as well as the issue of European integration. Using survey data from the Belgian National Election Study 2014, the study covers two research objectives. First, we investigate the role of feelings of resentment in citizens' support for the EU. We theoretically distinguish three constitutive components of resentment – status insecurity, relative deprivation and powerlessness – and empirically test to what extent these feelings drive negative attitudes towards the EU. Second, we uncover how Euroscepticism is embedded in a populist 'politics of resentment', paving the way for further inquiry into how the effect of resentment on Euroscepticism is mediated by different types of blame attribution. Our results reveal that feelings of social resentment translate into stronger Euroscepticism. However, the effect on Euroscepticism is primarily mediated by cultural (anti-immigrant) and political (anti-establishment) blame attributions. In this regard, the study presents a more detailed understanding of the roots and processes that drive mass Euroscepticism.